Antioxidant and Antimicrobial activity of Croton caudatus Geisel - Lokendrajit, N.; Indira, S.; Swapana, N.; Singh, C.B. (Asian Journal of Chemistry, 2012)
In this study different extracts of the leaves of Croton caudatus Geisel was evaluated for their antioxidant and antibacterial activity against human pathogenic gram +ve and gram –ve bacteria and antifungal activity against both human and plant pathogens. All the extracts exhibited varied levels of antibacterial and antifungal activity. The ethanolic extract shows antibacterial effect against all the tested bacteria with a diameter zone ranges from 8-12 mm. The ethanol extract of Croton caudatus leaves presented a good activity against Staphylococcus aureus and Pseudomonas putida with 12 mm inhibition zone diameter whereas methanolic extract presented a good activity against Candida albicans. Chloroformic and ethanolic extracts of Croton caudatus exhibited inhibition zone diameter of 10 and 12 mm, respectively against Microphomina phaseolina. The results obtained in this study appears to confirm the antioxidant and antimicrobial potential of Croton caudatus leaves and thereby may be useful in the treatment of diseases.